KEWAJIBAN DEBITUR UNTUK MENGASURANSIKAN BARANG AGUNAN DENGAN HAK TANGGUNGAN DALAM PERJANJIAN KREDIT DI BANK PEMERINTAH DAN SWASTA - DAULAT TARIGAN (PREMISE LAW JURNAL, 2015)
Credit contract, using hypothecation, between a debtor and a Bank as the creditor requires the debtor to mortgage his belonging as the collateral for paying off his debt. The research was descriptive analytic, using judicial normative method. In the implementation of insurance contract, a debtor is represented by a Bank as the creditor in signing the covering if the insurance, but the obligation related to the insurance contract is imposed on the debtor. The Bank and the Insurance Company never disclose the debtor’s right, and the even try to cover it up. The implementation of the claim for the insurance which will be filed by the should meet the provisions in the contract which has been agreed by the guarantor and the guarantee. Keywords: Bank Credit Contract, Insurance, Collateral